Review of the CPWF small grants initiative - Woolley, Jonathan N. (CGIAR Challenge Program on Water and Food, 2011)
This working paper reviews the experiences of the Challenge Program on Water and Food (CPWF) with 14 “small grants for impact” that were contracted in early 2006 and operated for periods of 12 to 18 months. For a total investment of under US$1 million – less than the equivalent of a typical 3-5 year CPWF research for development project in Phase 1, the small grant projects made significant contributions to identifying water and food technology for specific end users (thus showing the potential of CPWF research in general); to better understanding of adoption; to stimulating research by nongovernmental organizations (NGOs) and to better connecting CPWF researchers in general to the reality of the development process. Four of the small grants were outstanding in their contribution across all four of these criteria; six others made significant contributions to one or more, representing a high success rate for the original investment. The quality of many of the 126 eligible proposals received was sufficient to have identified at least 20 more projects suitable for immediate funding at that time in late 2005. Unfortunately, other demands on CPWF funding and priorities on research set by the Consortium Steering Committee made it impossible to support these. This review concludes that calls for small grant proposals are an effective way of obtaining local impact and of connecting a wide range of relevant institutions to the efforts of a network such as CPWF